Utilizing hydrophobic sand to construct an air permeable aquiclude to enhance rice yields - Jing Wu; Xiaoyan Ma; Yuming Su; Shengyi Qin; Francesco Pilla (Scientific Reports)
Abstract The Chinese government attaches great importance to the ecological restoration of abandoned open-pit mines, increasing the area of cultivated land, and ensuring food security. Soil reconstruction is a crucial step in ecological restoration of abandoned open-pit mines. This study investigated the utilization of hydrophobic sand to create an Air-Permeable Aquiclude (APAC) under the plant root zones, thereby minimizing water infiltration and enhancing soil aeration. Field plot experiments for 2 years have been conducted, with control groups, Clay Aquitard (CAT), and Plastic Aquiclude (PAC), to evaluate the effects of APAC on rice yield, nitrogen utilization, and water efficiency. The findings revealed that utilizing APAC resulted in a significant rise in rice yield, ranging from 8.09 t/hm² to 9.27 t/hm², which were 7.67–27.16% higher than the control groups. Moreover, the APAC led to a remarkable reduction in irrigation water usage by 37.08%, alongside a substantial boost in Irrigation Water Productivity (IWP) efficiency by 28.64–71.12%. Notably, Nitrogen Partial Factor Productivity (NPFP) exhibited a substantial increase of 7.69–27.06%. These outcomes underscore the APAC’s positive role in water and nutrient conservation and enhanced yields.